Burden of comorbidities in people with multiple sclerosis: a population-based study in Catalonia - Mora, Toni (Frontiers in Neurology, 2025)
BackgroundPeople with multiple sclerosis (MS) often present with chronic comorbidities that complicate care and affect prognosis. Population-based evidence in Europe is limited.ObjectiveTo describe the prevalence of selected comorbidities among individuals with MS in Catalonia, Spain, using administrative health records.MethodsWe analysed data from 9,998 people diagnosed with MS (2013–2017), including demographic and diagnostic information across all care levels. Prevalence estimates for 23 comorbidities were stratified by age and sex, and, where available, compared with those of the general population.ResultsThe MS population had a higher prevalence of psychiatric, metabolic, and autoimmune comorbidities in all age groups. Young women (18–40 years) showed increased rates of depression, anxiety, thyroid disease, and migraine, while middle-aged men (50–60 years) had higher rates of hypertension, hyperlipidaemia, and diabetes.ConclusionMS is associated with a substantial, early-onset comorbidity burden, underscoring the need for integrated, multidisciplinary care across the life course.